Usnic acid induces apoptosis via an ROS-dependent mitochondrial pathway in human breast cancer cells in vitro and in vivo. Issue 1 (1st December 2014) - Zuo, Shu-ting; Wang, Li-ping; Zhang, Yan; Zhao, Dan-ning; Li, Qiong-shu; Shao, Dan; Fang, Xue-dong
Abstract : Usnic acid induces ROS-dependent mitochondrial mediated apoptosis in human breast cancer MCF-7 cells in vitro and in vivo . Abstract : Usnic acid (UA), an active dibenzofuran derivative mainly found in lichens, is considered an antineoplastic agent based on its activity against tumor cells. However, the exact molecular mechanism through which UA mediates this activity has yet to be elucidated. Here, we have shown that UA selectively inhibited the viability of human breast cancer MCF-7 cells in a concentration- and time-dependent manner. UA provoked the generation of reactive oxygen species (ROS), which triggered the mitochondrial/caspase apoptotic pathway in MCF-7 cells. N -Acetylcysteine (NAC) blocked the generation of ROS, which reduced the stimulation of apoptotic mechanisms including activation of c-Jun-N-terminal kinase (JNK), loss of mitochondrial membrane potential (MMP), release of cytochrome-c, and activation of the caspase–cascade. Moreover, UA markedly inhibited tumor growth in a dose-dependent manner in MCF-7 tumor-bearing mice without inducing significant toxicity. Taken together, these findings suggested that UA stimulated apoptosis through an ROS-dependent mitochondrial pathway in MCF-7 cells.